Development of iron-rich whey protein hydrogels following application of ohmic heating – Effects of moderate electric fields. (September 2017) - Pereira, Ricardo N.; Rodrigues, Rui M.; Altinok, Emir; Ramos, Óscar L.; Xavier Malcata, F.; Maresca, Paola; Ferrari, Giovanna; Teixeira, José A.; Vicente, António A.
Abstract: The influence that ohmic heating technology and its associated moderate electric fields (MEF) have upon production of whey protein isolate cold-set gels mediated by iron addition was investigated. Results have shown that combining heating treatments (90 °C, 5 min) with different MEF intensities let hydrogels with distinctive micro and macro properties – i.e. particle size distribution, physical stability, rheological behavior and microstructure. Resulting hydrogels were characterized (at nano-scale) by an intensity-weighted mean particle diameter of 145 nm, a volume mean of 240 nm. Optimal conditions for production of stable whey protein gels were attained when ohmic heating treatment at a MEF of 3 V ∙ cm − 1 was combined with a cold gelation step using 33 mmol ∙ L − 1 of Fe 2 + . The consistency index of hydrogels correlated negatively to MEF intensity, but a shear thickening behavior was observed when MEF intensity was increased up to 10 V ∙ cm − 1 . According to transmission electron microscopy, ohmic heating gave rise to a more homogenous and compact fine-stranded whey protein-iron microstructure. Ohmic heating appears to be a promising technique, suitable to tailor properties of whey protein gels and with potential for development of innovative functional foods. Graphical abstract: Highlights: A new method for the production iron-rich whey protein hydrogels is proposed. Ohmic heating and iron cold-gelation were combined to produce protein hydrogels Incorporation of significant amounts of iron within protein network were allowed Electrical heating influenced properties iron-rich whey protein hydrogels